Pretreatments of Broussonetia papyrifera: in vitro assessment on gas and methane production, fermentation characteristic, and methanogenic archaea profile - Lifeng Dong; Yanhua Gao; Xuelan Jing; Huiping Guo; Hongsen Zhang; Qi Lai; Qiyu Diao (Animal Bioscience, 2022)
Objective The present study was conducted to examine the gas production, fermentation characteristics, nutrient degradation, and methanogenic community composition of a rumen fluid culture with Broussonetia papyrifera (B. papyrifera) subjected to ensiling or steam explosion (SE) pretreatment. Methods Fresh B. papyrifera was collected and pretreated by ensiling or SE, which was then fermented with ruminal fluids as ensiled B. papyrifera group, steam-exploded B. papyrifera group, and untreated B. papyrifera group. The gas and methane production, fermentation characteristics, nutrient degradation, and methanogenic community were determined during the fermentation. Results Cumulative methane production was significantly improved with SE pretreatment compared with ensiled or untreated biomass accompanied with more volatile fatty acids production. After 72 h incubation, SE and ensiling pretreatments decreased the acid detergent fiber contents by 39.4% and 22.9%, and neutral detergent fiber contents by 10.6% and 47.2%, respectively. Changes of methanogenic diversity and abundance of methanogenic archaea corresponded to the variations in fermentation pattern and methane production. Conclusion Compared with ensiling pretreatment, SE can be a promising technique for the efficient utilization of B. papyrifera, which would contribute to sustainable livestock production systems.